The Dental Students’ Compliance To The Covid-19 Health Protocols In Private Universities In Indonesia: Cross-Sectional Survey - Lisa prihastari; Rozalinda; Adzkia Dheyatika Asri; Riki Wira Laksana; Vio Nica Fisri; Sonya Priyadharsini (Universitas Muhammadiyah Yogyakarta, 2025)
The COVID-19 pandemic has brought about extensive changes in human lifestyles as individuals adopt preventive measures through health protocols. Dental students, playing a pivotal role in society, are particularly instrumental in implementing these protocols within their families and communities. This study aims to evaluate the compliance of dental students with COVID-19 protocols at five private universities in Indonesia and explore associated factors. This study was carried out by distributing validated online questionnaires to college students enrolled in undergraduate and professional dental programs. The questionnaire encompassed five questions assessing the adherence to COVID-19 preventive measures gained from 706 participants and was analyzed using statistical methods, including chi-square and multivariate logistic regression. Descriptive analysis revealed that 51.1% of students adhered to COVID-19 protocols. Notably, female students exhibited significantly higher compliance, with an odds ratio of 2.361 (p < 0.001). On the contrary, variables such as student group, academic year, parental education levels, family size, and the presence of vulnerable family members showed no significant associations (p ≥ 0.05). Gender and students' comorbid disease history emerge as influential factors affecting their compliance with COVID-19 protocols.